1998
DOI: 10.2337/diabetes.47.3.457
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and the expression of endothelial nitric oxide synthetase in diabetic neuropathy, vascular disease, and foot ulceration.

Abstract: We studied endothelial-mediated microvascular blood flow in neuropathic diabetic patients to determine the association between endothelial regulation of the microcirculation and the expression of endothelial constitutive nitric oxide synthetase (ecNOS) in the skin. Vasodilation on the dorsal foot in response to heating and iontophoresis of acetylcholine (endothelium-dependent) and sodium nitroprusside (endothelium-independent) were measured using single-point laser Doppler and laser Doppler imaging in diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
247
6
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(273 citation statements)
references
References 27 publications
17
247
6
3
Order By: Relevance
“…It was suggested that this could be a contributing factor to the endothelial cell dysfunction observed in diabetic patients. We have confirmed the finding that diabetic patients have lower ecNOS than control subjects, however, in another study [24], the activity of ec-NOS at the site of ulceration was not determined. We have therefore extended these observations by showing raised ecNOS and iNOS in DFU patients.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It was suggested that this could be a contributing factor to the endothelial cell dysfunction observed in diabetic patients. We have confirmed the finding that diabetic patients have lower ecNOS than control subjects, however, in another study [24], the activity of ec-NOS at the site of ulceration was not determined. We have therefore extended these observations by showing raised ecNOS and iNOS in DFU patients.…”
Section: Discussionsupporting
confidence: 77%
“…It would, however, be difficult to obtain samples to determine NOS activity in non-treated diabetic patients. It has recently been shown that ecNOS immunoreactivity in the skin of diabetic neuropathic patients and diabetic patients with neuropathy and vascular disease are reduced compared with control subjects [24]. It was suggested that this could be a contributing factor to the endothelial cell dysfunction observed in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have assessed small fiber dysfunction indirectly by assessing abnormalities in skin blood flow, and although some have shown an abnormality18, others have not17, 33. In the present study, we have shown widespread small fiber damage with a marked loss of corneal nerve fibers and sudomotor dysfunction in both the hands and feet of patients with CN compared to patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 38%
“…Indeed, there is a substantial literature on the role of non‐synaptically released substance P and CGRP, regulating osteoblast and osteoclast proliferation15, and inhibiting pro‐inflammatory cytokines16, key players in the pathophysiology of CN. Whereas in a study of 23 patients with CN, small fiber integrity, assessed by the hyperemic response to heating skin, was found to be preserved17, a subsequent study from the same group showed an impaired nerve–axon reflex in patients with CN18. More direct bone biopsy studies have shown reduced expression of CGRP in the bone of patients with CN compared to patients with diabetic neuropathy only19.…”
Section: Introductionmentioning
confidence: 94%
“…[1][2][3][4] A number of hemodynamic and metabolic disturbances affect the structure and function of the heart in patients with CKD. 5 To compensate for the hemodynamic and metabolic alterations, an excessive increase in the left ventricular mass (LVM), a condition that has been termed 'inappropriate LVM' , is frequently found in patients with CKD. 6 The predicted LVM based on sex, height 2,7 and hemodynamic load can be used as an appropriate reference for the observed LVM.…”
Section: Introductionmentioning
confidence: 99%